IPLEMENTASI PEMBELAJARAN BERBASIS INFORMATION COMMUNICATION AND TECNOLOGY(ICT) PADA MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI MODEL TERPADU MADANI - M. Djafar Supriadi (Multilingual, 2016)
This research aims (1) to know and to analyse the availability of ICT resources at publicjunior high school of integrated model Madani; (2) to know and to analyse theimplementation of Indonesian language based on ICT learning in pioneering school ofintegrated model Madani; and (3) to know and to analyse student intersctions in ICTbased learning model. This research uses descriptive qualitative approach that is bydescribing the characteristic of variables using frequency tables and percentage. Dataare collected througt interview, observation, and documentation. Questionnaire isdesigned using likert scale. The result of this research shows that (1) the availability ofICT resources at public junior high school of integrated model Madani have anadequate amount, (2) the implementation of Indonesian language based on ICT learninghave not in edeal condition yet, but they have mostly perform KTSP learning principles,and (3) student interactions in ICT based learning model have develoved the CBSAmethod.